STUDI POTENSI LIMBAH KOTA SEBAGAI PEMBANGKIT LISTRIK TENAGA SAMPAH (PLTSa) KOTA SINGKAWANG - ., URAY IBNU FARUQ (Faculty of Engineering, Universitas Tanjungpura, 2016)
Abstract - Source of electrical energy is currently the main problems in Singkawang city, this is because the number of population density increased annually. Besides, the problem of the amount of waste continues to rise, these two problems can be solved with one solution to convert a renewable energy that makes a potential where trash converted into power plant of waste to energy. To determine whether the waste can be a solution to the energy crisis by conducting a study of potential waste or garbage into fuel power plant. writing this essay described how rubbish can produce electrical energy for 24833.76 kWh / day if operating for one year amounted to 9,064,322.4 kWh / year or 9064.32 MWh / year, The first step is to know the total amount of organic waste per day, the number of calories in the organic waste, the amount of energy (kWh) / day, the capacity of power generation, the power output of the boiler, steam turbine net power. Kata kunci : garbage of potential study, waste to energy, steam of power plant